Retrospect and Risk Analysis of Foot-and-Mouth Disease in China Based on Integrated Surveillance and Spatial Analysis Tools - Chen, Jiahui; Wang, Jianying; Wang, Minjia; Liang, Ruirui; Lu, Yi; Zhang, Qiang; Chen, Qin; Niu, Bing (Frontiers in Veterinary Science, 2020)
Foot-and-mouth disease (FMD) is a highly contagious disease of livestock worldwide, and FMD outbreaks have become a serious obstacle for the development of animal husbandry. To explore the distribution characteristics and transmission of FMD between 2010 and 2017 in China, Global Moran's I test and Getis-Ord Gi index were used to analysis the spatial cluster; Space-time permutation scan statistic was applied to analysis spatio-temporal pattern; GIS-based method was employed to create a map representing the distribution pattern, directional trend and hotspots for each outbreak. We also constructed a phylogenetic tree to compare the homology and variation of FMDV (Foot-and-mouth disease virus) which provide a clue for development of safety and effectiveness of vaccines. The results indicated that the FMD outbreak in China has obvious time patterns and a certain cluster in space and space-time; FMD outbreaks were concentrated in the first half of each year. The outbreaks of FMD were decreased each year from 2010 with an obvious downward trend of hotspots. Spatial analysis revealed that the distribution of FMD outbreaks in 2010, 2015 and 2017 exhibited a clustered pattern. Space-time scanning showed that spatio-temporal clusters center was found in Guangdong, Tibet and the junction of Wuhan, Jiangxi, Anhui. After comparing spatial analysis and space-time analysis of FMD outbreaks, it can be found that Guangdong was the same cluster of the two in 2010. In addition, the directional trend analysis indicated that the FMD transmission was oriented toward northwest-southeast. It can be found that FMDV in China can be divided into three pedigrees and the homology of these strains is very high by comparing the first FMDV strain with other FMDV strain.